Never bring a knife to a gunfight? Lethality of weapon use in Dutch homicides - Krüsselmann, Katharina (European journal of criminology, 2025)
Firearm violence is a serious issue in Europe, yet the validity of existing theoretical approaches to weapon use in violent encounters have not been explicitly tested in the European context. This study tested existing hypotheses on weapon use and lethality ? the Adversary Effects Hypothesis, the Physical Strength Hypothesis, and the Social Distance Hypothesis ? using homicide data from the Netherlands, where detailed data on weapon use in homicide are available. Based on these hypotheses, we expected victim characteristics and the social distance between the victim and perpetrator to affect the modus operandi. However, our results do not align with these expectations when situational control variables are included. We conclude that existing studies on weapon lethality have a limited generalizability due to their assumption of free weapon choice. This is only met in contexts in which legal availability of firearms is high, which is not the case in the Netherlands. In addition, the hypotheses focus too narrowly on victim characteristics, without accounting for the situational factors influencing violent encounters. Based on these insights, we provide suggestions for theoretical and empirical improvements on firearm violence research.